KEANEKARAGAMAN TERATOMA OVARIUM - Lintong, Poppy M. (UNIVERSITAS SAM RATULANGI, 2011)
Abstract: Ovarian teratoma is a germinal cell tumor derived from fetal yolk sac germinal cells. This tumor can occur in gonads and extragonads. Its frequency is around 25%, which is less than 40% for sacrococygeal teratoma. According to WHO’s classification, ovarian teratoma is divided into three groups: immature, mature, and monodermal teratoma. Among these groups, the dermoid cyst has the highest incidence of all ovarian tumors (26-44%); and 85% of these have an age range of 20-56 years. But the other kinds of teratoma are rarely found. Clinicopathological aspects of teratomas are very unique, since these tumors develop from totipotential germinal cells. If these germinal cells differentiate along the embryonic line, then the tumor will consist of three components: ectoderm, endoderm, and mesoderm. As a result of this, the tumors show a variety of morphologies. A monodermal teratoma, e.g. an ovarian struma or a carcinoid tumor, contains only one component. Clinically, ovarian teratoma manifests itself as a mass in the ovarium, with accompanying pain, abdominal distention, or emesis. However, mostly there is no palpable mass in the abdomen, and clinical signs and symptoms manifest themselves later. The tumor can be detected earlier in case of an ovarian torsion. Key words: teratoma, mature, immature, monodermal. Abstrak: Teratoma ovarium merupakan tumor sel germinal yang berasal dari sel-sel germinal yolk sac fetus. Tumor ini dapat ditemukan pada gonad dan ekstragonad. Frekuensi teratoma ovarium sekitar 25%, sesudah teratoma sakrokoksigeal 40%. Menurut klasifikasi WHO teratoma ovarium dibagi atas tiga kelompok: teratoma imatur, matur, dan monodermal. Di antara ketiga jenis teratoma ovarium ini, kista dermoid mempunyai insiden tertinggi (26%-44%) dari semua tumor ovarium; dan 85% penderita berusia antara 20-56 tahun. Jenis lain sangat jarang ditemukan. Aspek klinikopatologik teratoma tergolong unik karena secara patogenesis teratoma berkembang dari sel-sel germinal totipotensial. Bila sel-sel germinal berdiferensiasi sepanjang garis embrionik, maka tumor biasanya terdiri atas tiga komponen, yaitu ektoderm, endoderm, dan mesoderm, dengan morfologi yang berbeda-beda. Teratoma monodermal (struma ovarium dan tumor karsinoid) terdiri dari satu komponen jaringan saja. Secara klinis teratoma ovarium ditandai oleh adanya massa pada ovarium, disertai nyeri, distensi abdomen, atau emesis. Walaupun demikian, umumnya jarang teraba massa dan gejala klinis timbul lambat. Diagnosis penyakit dapat ditegakkan lebih dini bila terjadi torsi ovarium. Kata kunci: teratoma, matur, imatur, monodermal.